The Bible on Location : Off the Beaten Path in Ancient and Modern Israel - Baretz, Julie (Book collections on Project MUSE., 2015)
In this innovative guidebook Julie Baretz takes readers to twenty-one off-the-beaten-path locations in Israel where Bible stories are said to have happened. At each site she sets the scene by relating the historical context of the event, then follows with the biblical text itself and her own lively commentary. Captivating and complex Bible characters bring the locations to life as they face social, ethical, and spiritual dilemmas not unlike our own today. Baretz's narratives draw on history, archaeology, academic scholarship, and rabbinic literature for interpretations that enhance the meaning.